Spatiotemporal dynamics of surface water extent in the Kano River Basin, Nigeria: an analysis using Landsat and Sentinel-2 multi-spectral imagery (2000–2025) - Udoka, Ubong Paulinus (International Conference “Environmental Engineering”, 2026)
The dynamics of surface water of semi-arid areas require monitoring to measure the resilience of hydrology to climatic fluctuations and human influence. The paper combines twenty-five years of multisensor remotely sensed data to study the spatiotemporal variations in surface water in the Kano River Basin (KRB), Nigeria, one of the largest irrigation-centred agricultural systems in West Africa. Google Earth Engine (GEE) was used to perform the Landsat (5, 7, 8, and 9) and Sentinel-2 imagery by using Cloud Shadow Screening (CSS) and the water extents (annually and seasonally) extracted using the Modified Normalised Difference Water Index (MNDWI) from 2000 through 2025. The dual hydrological regime in the occurrence of water, transition of gains and losses and trend shows a stable, permanent water, which is maintained by the input of groundwater and reservoirs and dynamic seasonal waters that are maintained by the input of monsoon rain. The findings contribute to managing irrigation, preparing for drought and sustainable administration of water as per the Sustainable Development Goals.
Keywords: surface water dynamics; MNDWI; remote sensing; semi-arid basin; Kano River Basin; water resources management